2019
DOI: 10.3390/su11216089
|View full text |Cite
|
Sign up to set email alerts
|

Visual Eye Gaze While Cycling: Analyzing Eye Tracking at Signalized Intersections in Urban Conditions

Abstract: The manner in which cyclists visually perceive elements of the urban environment plays an important role in bicycle crashes, which have been increasing in recent years. Yet, how visual information is processed by the user while riding a bike is still poorly analyzed by researchers. This study investigates cyclists’ eye gaze behavior at signalized intersections taking into account a set of gaze characteristics. Recording cyclist’s visual fixations by mobile-eye glasses in a real outdoor environment, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Our study was simple but relatively unique in the literature. To our knowledge, only a small number of outdoor studies with pedestrians or cyclists have been published so far, mostly focusing on locomotion and interactions with other pedestrians rather than interactions with vehicles in an unstructured environment (e.g., Arai et al, 2017;Fotios et al, 2015;Liu, Dong, Zhan, Wang, & Meng, 2020;Mantuano, Bernardi, & Rupi, 2017;Rupi & Krizek, 2019;Simpson et al, 2019;Trefzger, Blascheck, Raschke, Hausmann, & Schlegel, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was simple but relatively unique in the literature. To our knowledge, only a small number of outdoor studies with pedestrians or cyclists have been published so far, mostly focusing on locomotion and interactions with other pedestrians rather than interactions with vehicles in an unstructured environment (e.g., Arai et al, 2017;Fotios et al, 2015;Liu, Dong, Zhan, Wang, & Meng, 2020;Mantuano, Bernardi, & Rupi, 2017;Rupi & Krizek, 2019;Simpson et al, 2019;Trefzger, Blascheck, Raschke, Hausmann, & Schlegel, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Eye-tracking has been widely used in studying users' visual perception and attention in different contexts. For example, research has shown that experienced and inexperienced bicyclists have a different perceived gaze at infrastructure treatments around intersections (Rupi and Krizek 2019). The latest virtual reality headsets, such as the HTC VIVE Pro Eye, have integrated eye tracking features, allowing for IVE researchers to incorporate eye tracking analysis within their studies.…”
Section: )mentioning
confidence: 99%
“…A majority of bicycle-motor vehicle collisions occur in urban areas, where the bicycle is used for daily trips, and approximately half of them take place at bicycle crossings [9][10][11][12][13][14]. The most frequent crossing path crashes are where a motorist failed to yield to a bicyclist, and bicyclist failed to yield at an intersection or mid-block [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%